Hubungan Konsumsi Makanan Olahan Daging Merah dan Lama Screen Time dengan Risiko Sindrom Metabolik pada Remaja di SMA Batik 1 Surakarta - Septiana Vannessa Putri; Dwi Sarbini (Yayasan Literasi Sains Indonesia, 2025)
Metabolic syndrome (MetS) is a collection of metabolic risk factors that increase the likelihood of cardiovascular disease and type 2 diabetes. Modern lifestyles, such as the consumption of processed red meat foods and high screen time duration, are thought to contribute to the increased risk of MetS in adolescents. The purpose of this study was to analyze the relationship between consumption of processed red meat foods and screen time duration with the risk of metabolic syndrome in adolescents at SMA Batik 1 Surakarta. This study used a cross-sectional design with a sample of 65 randomly selected adolescents. Data on consumption of processed red meat foods were obtained through the Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ), while screen time duration was collected using a questionnaire. Metabolic syndrome was determined based on the National Cholesterol Education Program Adult Treatment Panel III (NCEP-ATP III) criteria. The results showed that there was a significant association between consumption of processed red meat foods and risk of metabolic syndrome in adolescents (p=0.007) and between screen time duration and risk of metabolic syndrome in adolescents (p=0.017). These findings indicate that diet and sedentary behavior play a role in increasing the risk of MetS in adolescents. Therefore, nutritional interventions and active lifestyle promotion are needed to prevent the incidence of metabolic syndrome among adolescents.